Mitochondrial dynamics reveal potential to facilitate axonal regeneration after spinal cord injury - Kaixuan Wang; Xi Chen; Mengmin Liu; Yunjuan Li; Yihua Zhu; Tiantong Zhou; Weiwei Tao; Yong Ma; Yang Guo; Lining Wang; Yue Hu (Journal of Translational Medicine)
Abstract Background Spinal cord injury (SCI) arises from traumatic damage to the spinal cord, resulting in varying degrees of sensory, motor, and autonomic dysfunction. Mitochondria, as the primary energy-producing organelles within cells, have garnered increasing attention for their critical role in promoting axonal regeneration following SCI. Aim of review This review aims to systematically examine the alterations in mitochondrial dynamics post-SCI and to elucidate their influence on axonal regeneration. Furthermore, the review evaluates the current challenges associated with SCI treatment and proposes potential therapeutic strategies for future research. Key scientific concepts of review The review comprehensively addresses mitochondrial dynamics, with a focus on key processes such as biogenesis, fusion and fission, mitophagy, trafficking, and anchoring. It delves into the molecular mechanisms by which signaling pathways within neurons and glial cells regulate these mitochondrial processes to facilitate axonal regeneration. Additionally, the review identifies existing challenges in SCI treatment and advocates for targeted interventions in mitochondrial dynamics as a promising therapeutic avenue, offering significant potential for advancing future research and treatment of SCI.